Familial Attendance at Indian Residential School and Subsequent Involvement in the Child Welfare System Among Indigenous Adults Born During the Sixties Scoop Era - Bombay, Amy; McQuaid, Robyn; Young, Janelle; Sinha, Vandna; Currie, Vanessa; Anisman, Hymie; Matheson, Kim (First Peoples Child & Family Review)

(untitled) (First Nations Child and Family Caring Society of Canada, 2020)
The health and wellness of Indigenous peoples continue to be impacted by the harmful colonization practices enforced by the Government of Canada. While the long-term health impacts of the Indian Residential School (IRS) system are documented, empirical evidence elucidating the relationship between the IRSs and the risk of offspring experiencing other collective childhood traumas, such as the Sixties Scoop (1950-1990) and the inequities within the child welfare system (CWS), is needed. Through an online study, we explored the links between familial (parents/grandparents) IRS attendance and subsequent involvement in the CWS in a non-representative sample of Indigenous adults in Canada born during the Sixties Scoop era. The final sample comprised 433 adults who self-identified as Status First Nation (52.2%), non-Status First Nation (23.6%), and Métis (24.2%). The study found that adults with a parent who attended IRS were more likely to have spent time in foster care or in a group home during the Sixties Scoop era. They were also more likely to have grown up in a household in which someone used alcohol or other drugs, had a mental illness or a previous suicide attempt, had spent time in prison, had lower mean levels of general household stability, and tended to have lower household economic stability. Moreover, the relationship between parental IRS attendance and foster care was explained, in part (i.e., mediated) by a higher childhood household adversity score. These findings highlight that the intergenerational cycles of household risk introduced by the IRS system contribute to the cycles of childhood adversity and increased risk of spending time within the CWS in Canada. This is the first study among Indigenous adults from across Canada to demonstrate quantitatively that being affected by the CWS during the Sixties Scoop era is linked to intergenerational cycles of risk associated with the IRS system.